COSO Framework-Based Internal Control in University Cooperatives and Its Impact on Financial Statement Quality - Ihrom Caesar Ananta Putra; Ratih Rakhmawati (Magister Akuntansi Universitas Pancasila, 2025)
Purpose: This study investigates the influence of COSO-based internal control components on the quality of financial statements in higher education cooperatives and explores implementation practices through quantitative and qualitative approaches. Methodology: A mixed-method design with a sequential explanatory strategy was employed. The quantitative phase applied SEM-PLS using SmartPLS 4.0 on 66 members of the STIE Mandala Cooperative. Exogenous variables included the control environment, risk assessment, control activities, information and communication, and monitoring, while the endogenous variable was financial statement quality. The qualitative phase involved in-depth interviews with supervisors, chairpersons, and treasurers, complemented by benchmarking with other university cooperatives. Finding: Quantitative results indicate that the control environment and monitoring significantly affect financial statement quality, whereas risk assessment, control activities, and information and communication show no significant effect. Qualitative insights reveal weak internal control implementation due to a trust-based culture, limited resources, and administrative procedures. Benchmarking highlights good practices such as stronger supervisory roles, formalized documentation, and the use of information technology to enhance control effectiveness. Implication: Strengthening the control environment and monitoring mechanisms is essential to improving cooperative financial reporting, supported by systematic risk management, consistent control activities, and effective communication. Originality: By integrating SEM-PLS analysis with qualitative insights and benchmarking, this study provides a comprehensive understanding of COSO Framework-based internal control effectiveness in university cooperatives.